The Relationship between Peer Social Support and the Learning Outcomes of BKPI IAIN Takengon Students - Risni Itawari; Birrul Walidani; Husrin Konadi (Institut Agama Islam Negeri Parepare, 2026)
This study aims (1) to describe the level of peer social support of BKPI IAIN Takengon students, (2) to determine the level of learning outcomes of BKPI IAIN Takengon students, (3) to determine whether there is an influence of peer social support on the learning outcomes of BKPI IAIN Takengon students. This study uses a quantitative approach with a correlational type. The study population was 156 students with a sample of 112 students determined using stratified random sampling techniques. Data collection techniques were carried out through questionnaires to measure peer social support and documentation in the form of Cumulative Achievement Index (GPA) data. Data analysis used descriptive tests, normality tests, and Pearson correlation tests. The results of the study showed (1) Descriptively, student peer support was in the fairly good to good category, with the majority in the range of 70–84, (2) the average value of learning outcomes was 3.67 in the satisfactory academic value, (3) That the correlation value between peer social support and learning outcomes was r = -0.059 with a significance value of p = 0.535 > 0.05. This indicates that there is no significant influence between peer social support and student learning outcomes. The conclusion of this study is that peer social support does not significantly influence the learning outcomes of BKPI IAIN Takengon students. Learning outcomes are more influenced by internal factors such as motivation, learning independence, and learning strategies. Nevertheless, peer social support still plays an important role in the social and psychological aspects of students.